METASYNTHESIS: ANALYSIS AND DESCRIPTION OF MATHEMATICAL REASONING CAPABILITY REVIEWED FROM COGNITIVE STYLE - Akbar Dakha Prabowo; Scolastika Mariani; Arief Agoestanto (STKIP Andi Matappa, 2024)
Reasoning is